Potential For Agricultural Biomass Production for Energy Purposes in Poland: a Review - Rafał Baum; Karol Wajszczuk; Benedykt Pepliński; Jacek Wawrzynowicz (Contemporary Economics, 2013)
This article reviews the production capacity of Polish agriculture with respect to biomass used for energy production. The forecast production potential of agricultural biomass in Poland in 2020 includes three key areas: the expected consumption of renewable energy according to energy type, the energy potential of agriculture and barriers to the use of biomass. Studies have shown that in Poland, total energy consumption will significantly increase (over 10% by 2020). Growth of demand for renewable energy will primarily result from strong growth of demand for transport biofuels and electricity. In 2020, approximately 80% of final energy from renewable sources will come from biomass. More than three-quarters of the biomass will be generated from agriculture. In Poland, crops from 1.0 to 4.3 million ha can be used for energy production. The study shows changes in the structure of biomass use, and the analysis confirms the declining share of biomass for heat production and the increasing share of biomass for electricity and biofuels. The main obstacles to the continued use of agricultural biomass are a lack of local markets for biomass energy and poor financial support for energy crop production.
Keywords: Q16; Q41; Q42; Q47; 330; biomass; biomass production; agricultural biomass; energy crops; biofuels